Konsep Estetika Impresionisme dalam Pemikiran Henri Bergson - Sri Pandanari, Dika (Indonesian Character Journal, 2025)
Since the eye and the ability of perception have been recognized in painting techniques, especially in representational painting, questions have emerged regarding how an artist’s perception of reality can be transferred into a work of art. This transfer of the artist’s perception into the artwork can be found in the Impressionist movement. Impressionism is a major art movement that revolutionized not only painting tools but also painting techniques and the paradigm of reality in the eyes of painters. Impressionism focuses on how light can define a moment in time, with color providing definition rather than black lines. From this definition, it is evident that the transfer of an artist’s perception is influenced by moments in time. One philosopher who discusses the moment in time is Henri Bergson. This study focuses on how an artist’s perception of reality can be expressed in the form of artwork, particularly within the Impressionist movement. The main issue explored is how an artist's perception is understood and processed into a work of art, by examining the influence of experiences of time, light, and color on the creation process. This research aims to outline the discussion of perception in Henri Bergson’s theory, especially in Impressionist painting. The study finds that at the very least, memory images are at play when the painter's perception is active, which in painting practice is referred to as "impression" in the Impressionist movement. Impressionism, grounded in the artist's connection with impressions of their reality, is, according to Bergson, an accumulation point of memory images contained within a person's memory and consciousness.